Islamic Law in Indonesia - Muhammad Hifdil Islam (Asy-Syari’ah : Jurnal Hukum Islam, 2018)
Introduction The enforcement of Islamic law in Indonesia has experienced ups and downs along with the political laws imposed by state power. Even behind all that, is rooted in the socio-cultural forces that interact in the political decision-making process. Nevertheless, Islamic law has progressed continuously. both through political infrastructure and political superstructure with the support of the socio-cultural force. Keywords: Islamic Law, Indonesia